Influence of NKG2C gene deletion and CCR5Δ32 in Pre-eclampsia—Approaching the effect of innate immune gene variants in pregnancy - Kaminski, Valéria de Lima; Ellwanger, Joel Henrique; Sandrim, Valeria [UNESP]; Pontillo, Alessandra; Chies, José Artur Bogo (My University, 2019)
Pre-eclampsia (PE) is a hypertensive disorder that affects an important number of pregnant women worldwide. The exact causes of PE remain poorly understood. However, inflammation and deregulation of innate immune cells, such as natural killer (NK) cells, contribute to PE pathogenesis. Besides, the mother's genetic background also impacts on PE susceptibility. Thus, genetic variants that potentially modify the behaviour of inflammatory cells may help us to understand the causes of PE. Variants of genes encoding NKG2C (expressed in NK cells) and C–C chemokine receptor type 5 (CCR5) (expressed mainly in leucocytes) are important targets in the study of gestational disorders. In this context, we evaluated the impact of both NKGC2 gene deletion and CCR5Δ32 gene variant on PE susceptibility in a population sample from central-southeast Brazil composed by 369 women (156 with PE and 213 healthy pregnant women). No statistically significant association between the NKG2C gene deletion and susceptibility to PE was observed. However, taking into consideration the important role of NK cells in pregnancy, the influence of NKG2C gene deletion on PE pathogenesis should not be ruled out and deserves further studies in populations with different genetic/ethnic backgrounds. In addition, our results regarding CCR5Δ32 corroborate previous data from our group approaching a distinct cohort and reinforce CCR5Δ32 as a protective factor against PE development (p < 0.05).
Keywords: CCR5; CCR5Δ32; inflammation; innate immunity; NK cells; NKG2C; Pre-eclampsia